A low computational cost optimization procedure for axial load carrying capacity of the multi-beam structure. (January 2023) - Kotšmíd, Stanislav; Beňo, Pavel
Highlights: Calculation assuming the equally long beams overestimates the load carrying capacity. Single beam FE analysis is used to find the optimized lengths within the tolerance. The load carrying capacity decreases for the optimized beam combination significantly. The load carrying capacity boundaries determine the field of experimental results. Abstract: The paper presents an improved algorithm to compute an axial load carrying capacity of the specific multi-beam structure in order to failure avoidance. The former approach based on the finite element method is reduced to determine a relation between the axial load and axial displacement for a single beam, while the time-consuming FE procedure applied on several beams is replaced with a numerical optimization process. The developed approach provides faster and simpler computation of the minimum axial load carrying capacity of the structure considering the beam length tolerances, where the results are in a good agreement with the complex FE analysis. Supporting theoretical and experimental analyses were performed to confirm the correctness of the mentioned method where the load carrying capacity of the multi-beam structure made up of six steel circular beams was analyzed.